Sireuma, a new genus of subterranean millipedes from the Iberian Peninsula (Diplopoda, Chordeumatida, Opisthocheiridae) - Reboleira, Ana Sofia P. S.
A new genus Sireuma is described to accommodate a new species, S. nobile, from a cave in Portugal. The unique features of the male gonopods and the absence of a postvulvar organ support the creation of a new genus. The new species is illustrated with scanning electron micrographs and diagrammatic drawings. Differences vis-à-vis its relatives are discussed, and information on the environment in which the new species was found is also provided.